Successful pregnancy using oral DHEA treatment for hypoandrogenemia in a 30-year-old female with 5 recurrent miscarriages, including fetal demise at 24 weeks: a case report - Boyle, Phil C.; Pandalache, Codruta; Turczynski, Craig (Frontiers in Medicine, 2024)
Hypoandrogenemia is not usually considered as a potential cause of recurrent miscarriage. We present the case of a 30-year-old female with 6 previous pregnancies resulting in one live birth and 5 pregnancy losses, including fetal demise at 24 weeks gestation. She had standard investigations after her 4 th loss, at a specialized miscarriage clinic. Lupus anticoagulant, anticardiolipin antibodies, thyroid function, parental karyotypes were all normal. Fetal products confirmed triploidy for her 4 th miscarriage at 16 weeks gestation. She was reassured and advised to conceive again but had fetal demise after 24 weeks gestation. This was her 5 th pregnancy loss with no explanation. She attended our Restorative Reproductive Medicine (RRM) clinic in January 2022. In addition to poor follicle function, we found hypoandrogenemia for the first time. Treatment included follicle stimulation with clomiphene and DHEA 25mg twice daily pre-conception with DHEA 20mg once daily maintained throughout pregnancy. She delivered a healthy baby boy by cesarian section at 36 weeks gestation in November 2023. Hypoandrogenemia should be considered as a contributory factor for women with recurrent miscarriage or late pregnancy loss. Restoration of androgens to normal levels with oral DHEA is safe and can improve pregnancy outcome.